Richard Korschefsky (1902-1946) und seine grundlegenden Arbeiten über Coccinellidae und die Larven der Coleoptera. - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 2007)
An overview of the life of Richard Korschefsky is presented, illustrated with photos. His work at the Deutsches Entomologisches Institut is given particular attention and his remarkable achievements in research on the Coleoptera: Coccinellidae reviewed. He treated the Coccinellidae in two parts of the Junk-Schenkling Catalogue (659 pages, 3279 species). As originator of a series of identification keys to the larvae of Coleoptera, he made five contributions which significantly improved our knowledge on these. A list of the publications of Richard Korschefsky is presented.